1-(Carboxymethyl)pyridinium chloride as an acidic ionic liquid for rice straw effective pretreatment. (November 2021) - Abdolmaleki, Amir; Nabavizadeh, Sayed Sajad; Badbedast, Mehran
Abstract: Herein, a suitable pretreatment based on an acidic ionic liquid was employed for superior enzymatic hydrolysis of rice straw, which is regarded as an inexpensive, easily accessible, and renewable agricultural waste. Using 1-(carboxymethyl)pyridinium chloride as an acidic ionic liquid, containing, both acetate and chloride groups, a superior penetration between cellulose chains and a proper dissolution can be easily achieved. Different analyzes, including FT-IR, XRD, and SEM, were conducted, indicating restructuring and increased free volume between cellulose chains in rice straw. Following the proper pretreatment with the ionic liquid, the next step in the fermentation and enzymatic hydrolysis process was well conducted, and promising results were attained for biofuel productions. The effects of water as a co-solvent, pretreatment time (2, 3, 5 h), temperature (25, 90, 120 °C), and solid loading (5, 6, 15% w/w) were investigated for maximum ethanol production. The best results were obtained in 35% water, at room temperature, and 6% (w/w) solid loading for 3 h. The hydrolysis yield in ethanol production was improved to 62.2% of the theoretical maximum.